Legal Protection for Buyers of Collateral Objects Sold at Auction - Joserando, Jodi Jordan; Maskanah, Ummi; Fuazi, Afif (Manunggal Halim Jaya, 2025)
The purpose of this research is to analyze the legal protection provided to buyers who purchase collateral objects sold at auction, as well as to explore the legal challenges faced by buyers in acquiring rights to these objects. The main focus of this research is to understand how the legal system provides protection for buyers. This study uses a qualitative method with a descriptive approach, aimed at describing and analyzing the legal situation in cases involving the auction of collateral objects. Data collection was carried out through interviews with various related parties, including notaries, legal practitioners, auction officials, and buyers of auctioned objects. The results of the study show that, although there are efforts to protect buyers under auction regulations, buyers often face challenges related to the legal status of the objects they purchase. Buyers are at risk of being caught in legal disputes concerning obligations attached to the purchased objects, especially with regard to third-party rights or debts associated with the object. This research also finds that the current auction procedures and regulations still have gaps that allow for legal uncertainty for buyers.